Glycerol Electrocatalytic Reduction Using an Activated Carbon Composite Electrode: Understanding the Reaction Mechanisms and an Optimization Study - Md. Rahim, Siti Aqilah Nadhirah; Lee, Ching Shya; Aroua, Mohamed Kheireddine; Wan Daud, Wan Mohd Ashri; Abnisa, Faisal; Cognet, Patrick; Pérès, Yolande (Frontiers in Chemistry, 2022)
The conversion of biomass-derived glycerol into valuable products is an alternative strategy for alleviating energy scarcity and environmental issues. The authors recently uncovered an activated carbon composite electrode with an Amberlyst-15 mediator able to generate 1,2-propanediol, diethylene glycol, and acetol via a glycerol electrocatalytic reduction. However, less attention to mechanistic insights makes its application to industrial processes challenging. Herein, two proposed intermediates, acetol and ethylene glycol, were employed as the feedstocks to fill the gap in the mechanistic understanding of the reactions. The results discovered the importance of acetol in producing 1,2-propanediol and concluded the glycerol electrocatalytic reduction process has a two-step reduction pathway, where glycerol was initially reduced to acetol and consecutively hydrogenated to 1,2-propanediol. At 353 K and 0.28 A/cm2, 1,2-propanediol selectivity achieved 77% (with 59.8 C mole% yield) after 7 hours of acetol (3.0 mol/L) electrolysis. Finally, the influences of the temperature, glycerol initial concentration, and current density on the glycerol electrocatalytic reduction were evaluated. The initial step involved the C-O and C-C bonds cleavage in glycerol plays a crucial role in producing either acetol or ethylene glycol intermediate. This was controlled by the temperature, which low to moderate value is needed to maintain a selective acetol-1,2-propanediol route. Additionally, medium glycerol initial concentration reduced the hydrogen formation and indirectly improved 1,2-propanediol yield. A mild current density raised the conversion rate and minimized the growth of intermediates. At 353 K and 0.21 A/cm2, glycerol (3.0 mol/L) electrocatalytic reduction to 1,2-propanediol reached the maximum yield of 42.3 C mole%.